Optical properties of gadolinia-doped cubic yttria stabilized zirconia single crystals. Issue 3 (1st February 2021) - Li, Siyao; Xu, Shoulei; Wang, Xiangyu; Wang, Daini; Goodman, Bernard A.; Hong, Xing; Deng, Wen
Abstract: Cubic zirconia single crystals stabilized with yttria and doped with Gd2 O3 (0.10–5.00 mol%) were prepared by the optical floating zone method, and characterized by a combination of X-ray diffraction (XRD), and Raman, electron paramagnetic resonance (EPR), ultraviolet–visible (UV–Vis), photoluminescence excitation (PLE) and photoluminescence (PL) spectroscopic techniques. XRD and Raman spectroscopy showed that the crystal samples were all in the cubic phase, whereas the ceramic sample consisted of a mixture of monoclinic and cubic phases. The absorption spectrum showed four peaks at 245, 273, 308, and 314 nm in the ultraviolet region, and the optical band gap differed between samples with ≤3.00 mol% and those with >3.00 mol% Gd2 O3 . The emission spectrum showed a weak peak at 308 nm and a strong peak at 314 nm, which are attributed to the 6 P 5/2 → 8 S 7/2 and 6 P 7/2 → 8 S 7/2 transitions of Gd 3+, respectively. The intensities of the peaks in the excitation and emission spectra increased with Gd 3+ concentration, reached a maximum at 2.00 mol%, then decreased with higher concentrations. This quenching is considered to be the result of the electric dipole-dipole interactions, and this interpretation is supported by the Gd 3+ EPR spectra, which showed progressive broadening with increasing Gd 3+ concentration throughout the concentration range investigated.